Developing a teaching method for animation creation: a quasi-experiment to assess creativity performance during the animation pre-production process - Abd Manan, Mohd Shahrudin; Wang, Xuefeng; Ramli, Saiful Hasley; Mohd Puad, Mohd Hazwan (Transnational Press London Limited, 2024)
The application of design thinking has been extensively used in the design and non-design sectors. There are numerous ways in which design thinking is applied and they vary depending on context. Existing research on complex animation design thinking is still relatively limited. Research on design thinking in animation can help inexperienced animators to create efficiently and avoid aimless creation patterns. The core of design thinking is human-centered problem-solving. Animation films as a kind of product serving the public, and many design details involved in its’ design process are also from a human-centered perspective. This study analyzes the nature of design thinking and uses creative methods as supporting tools to form a framework of animation design thinking for a teaching method. The framework was divided into three phases: the problem analysis stage (dominated by rational thinking), the idea generation stage (dominated by perceptual thinking), and the specialized information processing stage (dominated by rational thinking). The framework will be used as a guiding strategy to guide and influence the thinking patterns of beginning animation designers in universities and colleges in Mainland China. Since the population involved in this study is mainly concentrated on animation beginners. The research method used in this study is a pretest-posttest design in a quasi-experimental design on two natural classes on campus, which are randomly assigned to the control group and experimental group, a total of 47 bachelor's degree students in an animation-related major program. The experimental data from the pretest and posttest were collected and analyzed quantitatively in a paired-sample T-test. The experimental results showed that the animation design thinking framework has a significant impact on student creativity in the comparative effects of the pretest and posttest